Design and fabrication of simple geometric patterns - Mohamed Azad. (2010)
This project aims to develop a system that would enable users to generate simple geometric designs for fabrication. Islamic motifs or arabesque design are used as a basis for this project since Islamic art uses repeated geometric patterns to form intricate designs this makes it a suitable reference and guide for this project.